2021
DOI: 10.1016/j.hlc.2020.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Secondary Prevention of Cardiovascular Disease and Outcomes Following the Survival of Acute Coronary Syndrome

Abstract: Previous studies have shown that women with acute coronary syndrome (ACS) are less likely to receive inhospital care such as revascularisation procedures and secondary prevention medications. Therefore, the aim was to determine if the rate of secondary preventive care and outcomes also differ by sex in patients with ACS at 6 and 12 months after discharge. Methods Of ACS patients recruited from 43 hospitals between 2009 to 2018, 9,283 were discharged alive and followed up at 6 months as part of the Cooperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Our findings are broadly consistent with previous studies within Australia. Registry data from 43 public hospitals nationwide showed that women hospitalised for ACS are less likely than men to be prescribed recommended medications at discharge, and follow-up self-report data indicated that women were 16% less likely than men to be using at least 75% of the recommended medications (aspirin, other antiplatelet, lipid-lowering medication, beta-blocker and ACE inhibitor/angiotensin II receptor blocker) at 12 months following hospitalisation ( Hyun et al, 2021 ). Results from a representative Australian cross-sectional sample found that more men (50%) than women (34%) with self-reported CVD were using lipid- and blood pressure-lowering medications, with 19% and 23%, respectively, using neither medication ( Banks et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings are broadly consistent with previous studies within Australia. Registry data from 43 public hospitals nationwide showed that women hospitalised for ACS are less likely than men to be prescribed recommended medications at discharge, and follow-up self-report data indicated that women were 16% less likely than men to be using at least 75% of the recommended medications (aspirin, other antiplatelet, lipid-lowering medication, beta-blocker and ACE inhibitor/angiotensin II receptor blocker) at 12 months following hospitalisation ( Hyun et al, 2021 ). Results from a representative Australian cross-sectional sample found that more men (50%) than women (34%) with self-reported CVD were using lipid- and blood pressure-lowering medications, with 19% and 23%, respectively, using neither medication ( Banks et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that healthcare providers tend to assign women to a lower CVD risk category than men with identical risk factors ( Mosca et al, 2005 , Turnbull et al, 2011 ), even in patients with established CVD ( Turnbull et al, 2011 ). Sex differences in medications prescribed following a CVD event have been shown even when women have more co-morbidities such as hypertension, diabetes, chronic kidney disease and previous cerebrovascular diseases, than men ( Hay et al, 2020 , Hyun et al, 2021 , Khan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations